Proceedings of the 18th LACCEI International Multi-Conference for Engineering, Education, and Technology: Engineering, Integrat 2020
DOI: 10.18687/laccei2020.1.1.431
|View full text |Cite
|
Sign up to set email alerts
|

Sistema de Gestión de la Investigación, Desarrollo Tecnológico e innovación (I+D+i) y Modelo de Investigación Formativa: Caso Ingeniería - UCV

Abstract: The training of engineering professionals is taking on new challenges in the global and regional context framed in a process of transformation and order in the Peruvian University System, where structural changes have been developed since the new University Law, the Institutional Licensing process of the Universities, the Institutional Accreditation, as well as Programs Accreditation, incorporating in all these Models the Research, Technological Development and Innovation. Processes and guidelines that are inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…An interesting approach based on an example of a Spanish organization was described by Salaz-Ruiz [120]. His results are similar to the challenges described in this paper.…”
Section: Discussionsupporting
confidence: 74%
“…An interesting approach based on an example of a Spanish organization was described by Salaz-Ruiz [120]. His results are similar to the challenges described in this paper.…”
Section: Discussionsupporting
confidence: 74%
“…Through the results, it was possible to demonstrate the relationship between the systematization of pre-professional practice and investigative skills, starting from the independent exploration of both variables in the chosen social areas that revealed their situation rooted toward the poorest and most inefficient levels, despite the policies of educational quality and accreditation in the university and non-university higher education in the Peruvian context (Salas-Ruiz, 2020). It is inferred that education has little impact.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the existence of regulatory documents and policies such as those referred to above, pre-professional practice has not been recognized as a source of knowledge or space to develop research skills, since the Pedagogical Institutes have limited themselves to integrating or articulating such areas (MINEDU, 2019) because they have not assumed them as concomitant elements. In the case of universities, it has been observed that practice and research work as differentiated and disjointed curricular areas, having to provide in the subjects of their curricula actions that lead to formative research within the framework of the reforms of the Education Model Quality for the Accreditation of Peruvian professional careers (Alvitres et al, 2014;Salas-Ruiz, 2020) and of university policies leading to research as one of its purposes (Julca, 2016;Arrieta and Avolio, 2020).…”
Section: Introductionmentioning
confidence: 99%